2000
DOI: 10.1016/s0378-1097(00)00110-5
|View full text |Cite
|
Sign up to set email alerts
|

Osmoregulated periplasmic glucans in Proteobacteria

Abstract: Large amounts of osmoregulated periplasmic glucans (OPGs) are found in the periplasmic space of Proteobacteria. Four families of OPGs are described on the basis of structural features of the polyglucose backbone. Depending on the species considered, OPGs can be modified to various extent by a variety of substituents. Genes governing the backbone synthesis are identified in a limited number of species. They belong to three unrelated families. OPG synthesis is subject to osmoregulation and feedback control. Osmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 22 publications
1
69
0
1
Order By: Relevance
“…Knockout of ndvB compromised the production of the extracellular cyclic b-(1,2)-glucan, but had no effect on the production of xanthan (Figs 2C and EV3A). As glucan is normally synthesized under low-osmotic conditions and accumulates in the periplasmic space of Gram-negative bacteria [17,19], we isolated glucan from the periplasmic fraction by sizeexclusion chromatography followed by analysis by HPLC and MALDI-MS. Furthermore, the growth defect exhibited by glucan-deficient ndvB mutant in medium containing DETAPAC, BPS, and DP could be rescued by addition of FeSO 4 but not by MnCl 2 or ZnSO 4 , which further corroborated the iron specificity of the growth defect (Figs 1A-F and EV1E-G; Appendix Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Knockout of ndvB compromised the production of the extracellular cyclic b-(1,2)-glucan, but had no effect on the production of xanthan (Figs 2C and EV3A). As glucan is normally synthesized under low-osmotic conditions and accumulates in the periplasmic space of Gram-negative bacteria [17,19], we isolated glucan from the periplasmic fraction by sizeexclusion chromatography followed by analysis by HPLC and MALDI-MS. Furthermore, the growth defect exhibited by glucan-deficient ndvB mutant in medium containing DETAPAC, BPS, and DP could be rescued by addition of FeSO 4 but not by MnCl 2 or ZnSO 4 , which further corroborated the iron specificity of the growth defect (Figs 1A-F and EV1E-G; Appendix Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Although glucan is localized primarily in the periplasm, several bacteria also produce secreted glucan [17,18]. We have found that extracellular supplementation of cyclic b-(1,2)-glucan could rescue the growth deficiency exhibited by the glucan-deficient Xcc mutants under iron-restricted conditions.…”
Section: Embo Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low molecular weight periplasmic glucans that have a linear or cyclic backbone structure are intrinsic components of some Gram-negative bacterial cell envelopes (Breedveld and Miller, 1994;Kennedy, 1996;Bohin, 2000). Typical amongst the -Proteobacteria is the production of structurally diverse cyclic glucans.…”
Section: C1 Occurrencementioning
confidence: 99%
“…Periplasmic glucans are considered to be important intrinsic components of the Gram-negative cell envelope since mutants defective in their synthesis display a variety of pleiotropic phenotypes suggestive of significant structural alteration of the cell envelope (Bohin, 2000;Breedveld and Miller, 1994;Kennedy, 1996). The glucans occur in the periplasm usually only during growth of the bacteria in a medium of very low osmolality (100 milliosmoles per kilogram H 2 O) and can accumulate to a high concentration (10-100 mM), representing 5-10% of the cellular dry weight (Bohin, 2000;Talaga et al, 2002).…”
Section: C21 Adaptation To Hypo-osmotic Conditionsmentioning
confidence: 99%